2015
DOI: 10.1158/0008-5472.can-15-0325
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Thermotolerance Impairs Nanoparticle Transport in Tumors

Abstract: The delivery of diagnostic and therapeutic agents to solid tumors is limited by physical transport barriers within tumors, and such restrictions directly contribute to decreased therapeutic efficacy and the emergence of drug resistance. Nanomaterials designed to perturb the local tumor environment with precise spatiotemporal control have demonstrated potential to enhance drug delivery in preclinical models. Here, we investigated the ability of one class of heat-generating nanomaterials called plasmonic nanoant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 52 publications
0
29
0
Order By: Relevance
“…Bagley et al demonstrated the use of plasmonic nanoantennae to enhance transport into a model of ovarian cancer via heat generation. They also used temperaturecontrolled microfluidic devices to measure diffusion of the nanoparticles in vitro [192]. The use of microfluidic devices to aid in the rapid development of translatable nanoparticles for TME studies is a very active and promising area of research.…”
Section: Transport and Delivery Of Nanoparticlesmentioning
confidence: 99%
“…Bagley et al demonstrated the use of plasmonic nanoantennae to enhance transport into a model of ovarian cancer via heat generation. They also used temperaturecontrolled microfluidic devices to measure diffusion of the nanoparticles in vitro [192]. The use of microfluidic devices to aid in the rapid development of translatable nanoparticles for TME studies is a very active and promising area of research.…”
Section: Transport and Delivery Of Nanoparticlesmentioning
confidence: 99%
“…Vascular structure, perfusion, and permeability continue to be key features captured by IVM, and IVM studies have been useful in parsing the influence of various cell populations including perivascular VEGF+ macrophages [64]; therapeutic adjuvants such as anti-VEGF treatment [226], radiation [227], ultrasound [228], and hyperthermia [47,229,230]; and NP physicochemical features such as size [50,219] and shape [231] impact transport from vasculature to the target tissue. Reporter GEMMs enable clear and simultaneous visualization of vascularity, for instance using Tie2-GFP GEMMs [230], and neighboring cell populations.…”
Section: The Nuts and Bolts Of Ivm Nanoparticle Imagingmentioning
confidence: 99%
“…Reporter GEMMs enable clear and simultaneous visualization of vascularity, for instance using Tie2-GFP GEMMs [230], and neighboring cell populations. As an example, a two-color GEMM that ubiquitously expresses membrane-anchored RFP, including in the endothelium, and GFP in CX3CR1+ phagocytes, was used to visualize NP transport from tumor vasculature to adjacent perivascular phagocytic cells [54].…”
Section: The Nuts and Bolts Of Ivm Nanoparticle Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Such microfluidic devices have been used to study various aspects of cancer progression such as tumor growth, presence of high interstitial fluid pressure, and cancer cell extravasation 18–24 . Such technological platforms have also been used to understand drug-tumor interactions such as drug specificity, penetration into cancer spheroids, and efficacy towards repressing cancer growth 20, 24–27 . Many of these platforms employ multi-layered or multi-channel devices to create a perfused tumor-a-on-chip system 18, 21, 25, 26 .…”
Section: Introductionmentioning
confidence: 99%